Pericytes Across the Lifetime in the Central Nervous System - Bennett, Hannah C.; Kim, Yongsoo (Frontiers in Cellular Neuroscience, 2021)
The pericyte is a perivascular cell type that encapsulates the microvasculature of the brain. Pericytes play a crucial role in the development and maintenance of the blood brain barrier (BBB), and has a multitude of important functions in the brain. Recent evidence indicates that pericyte impairment has been implicated in neurovascular pathology, associated with various human diseases, such as diabetes mellitus, Alzheimer’s disease and stroke. Although the pericyte is essential for normal brain function, knowledge about its developmental trajectory and anatomical distribution is limited. This review summarizes the scientific community’s current understanding of pericytes’ regional heterogeneity in the brain and their changes during major life stages. More specifically, this review focuses on pericyte differentiation and migration during brain development, regional population differences in the adult brain, and changes during aging. Most of what is known about pericytes comes from studies of the cerebral cortex and hippocampus. Therefore, we highlight the need to expand our understanding of pericyte distribution in the whole brain to better delineate this cell type’s role in the normal brain and pathological conditions.